The Impact Of Physical Sports Activities In The Collective Development Of Some Mental Skills Among Middle School Students (13-15 Years). - Saidia, Houari; Messaoudi, Khaled; Beneddine, Kamel (Université de M'sila, 2017)
Physical activity is one of the most important public activities within the educational programs, which aim to prepare the individual for a society that is useful, and sports activities are the most important physical activities and sports are the basis for the health of objects and the safety of minds, but its place in the care of members of society and Education is so that it goes along with the movement of education at every stage, and perhaps the most important stages of education is the intermediate stage, which is an enthusiasm passes through the individual during the development of social and physical, mental and psychological. In the educational program of physical education and sports, we find that the collective sports activities take a large area of attention to adolescents in view of the positive implications for them, as well as their contribution to satisfy their needs and desires, which explains their interest in them, which indicates that they respond to many of their individual needs. The existence of the group in these activities, which in turn lead to the development of mental skills of the student in the spirit of sports, which in turn earn many of the qualities of educational and moral high In this research, we will explore the impact of collective sports physical activity on the development of some mental skills among middle school students.
Keywords: physical sports activities; collective sports activities; mental skills; middle school students